Effective Development of Real Estate Market Resilience in Ireland Amidst Economic Shocks - Megha, (Digital Repository of Theses, 2025)
Background: In this paper the author discusses the impact of economic shocks on the Irish real estate market and the pressing issues of the housing crisis in Ireland. The residential as well as the commercial property prices have been skyrocketing all over Ireland and there is a dearth of affordable housing for the common people. This has increased the homelessness in Ireland to an alarming levels. Objectives: This study will not just analyse the role of the major players in the real Estate industry in Ireland, but also the key factors that influenced it during the times of socio- economic shocks like the crisis of 2008, COVID-19 and Brexit. It will also compare the different trend of the Irish market against other European countries. The author will also asses the current regulations governing the industry and explore any potential solutions that can be implemented to bring stability to the otherwise unstable market. Methods: A mixed method was employed by the author to determine the current trends in the market and the how the industry behaves during the economic shocks. Quantitative data from the CSO and Eurostat was collected to do the statistical analysis while qualitative data from the secondary sources were applied to do a detailed Thematic analysis of the Irish real estate market. Result: The findings shed a quality light to reveal that construction costs have risen tremendously over the past decade. Institutional investment in rental housing has grown, impacting market affordability, Due to this Investors diversified portfolios and shifted to safer assets during economic downturns. The impact of economic shocks like COVID-19, promoted urban-to-rural migration surges, affecting demand and pricing in both regions. Conclusion: The research emphasises on the vitality of the Irish real estate market depending on both global economy and the presence of FDI. The government’s response through policy frameworks such as the National Recovery and resilience plan has been positive but needs to go further and adapt greatly to the need of sustainable green housing policies that prioritizes combined efforts of the governmental bodies and the Private investors. The long-term impacts resulting from sky-high construction costs and the lower housing affordability suggests that the market is not stable to handle any major shock and there are structural problems that make the market vulnerable.